Tariqa Haq Naqsyabandi As a System of Islamic Iman Building in Pontianak, West Kalimantan - Muh. Gitosaroso; Sulkhan Chamim; Muhammad Masruri (Religia, 2022)
Tariqa (Eng.: Order; Tariqa) is known as an organization that only focuses on spiritual development. That is why Tariqa adherents are often trapped in rituals, which sometimes distance them from the outlined Islamic Iman. This study aims to determine the extent to which the Tariqa can become a system of Iman formation. This research was conducted in one of the largest Tariqas in Pontianak, namely the Tariqa Haq Naqsyabandi, which is headquartered at Perum IV Pontianak City. Based on the results of the research, using a qualitative approach with phenomenological type, it was found that: 1) The Tariqa Haq Naqsyabandi has been carrying out Iman-building since the beginning of the congregation's declaration (Bai’at) of joining this Tariqa; 2) Follow-up coaching is carried out at certain times, such as Tawajjuhan, Special Teaching, Level Ups, and Incidental Teaching